ANALISIS PENERAPAN METODE MUHADATSAH DALAM PEMBELAJARAN MAHARAH KALAM SISWI DI PONDOK PESANTREN TAHFIZH WADI AL-QURAN PADANGSIDIMPUAN - Idam Kholid Nasution; Fatiah Lubis; Abdul Sattar Daulay (CV. Bunda Ratu, 2026)
Arabic speaking ability is one of the essential skills in Arabic language learning that should be developed throughcontinuous communication practice. This study aims to analyze the implementation of the muhadatsah method inimproving students' maharah kalam (speaking skills) and to identify the factors that support their Arabic speakingability at Ma'had Tahfiz Wadi Al-Qur'an Padangsidimpuan. This research employed a descriptive qualitativeapproach, with data collected through observation, interviews, and documentation. The findings indicate that theimplementation of the muhadatsah method consists of several stages, namely presenting hiwar (dialogue)materials, listening to and repeating conversations, understanding vocabulary (mufradat), practicing speaking,and conducting evaluations. The implementation of this method contributes to the improvement of students'maharah kalam, particularly in speaking fluency and confidence in using Arabic. The supporting factors includean Arabic-speaking environment, habitual use of Arabic in daily activities, the role of the teachers (ustadzah),and peer support.